Pulmonary glue embolism after radiological embolization of pelvic varices: a case report - Elise Longueville; Sandra Dury; Julien Ancel; Jonathan Attali; Rahma Larad-Riffault; Camille Pierrot; Jeanne-Marie Perotin; Gaetan Deslee (BMC Pulmonary Medicine)
Abstract Background Non-thrombotic pulmonary embolism (NTPE) is defined as embolization in the pulmonary circulation of biological or non-biological substances and foreign bodies. The migration of glue in the pulmonary circulation during interventional procedures is unusual and has been reported mainly after gastroenterological procedures. The most severe cases of NTPE can be life-threatening. Case presentation A 31-year-old woman developed respiratory failure 24 h after radiological embolization of pelvic varices. Glue embolization was detected during the intervention and was confirmed on a chest CT scan showing multiple bilateral hyperdense elements up to sub-pleural regions. The patient developed respiratory symptoms 24 h after the procedure, progressively worsening with oxygen requirement up to 6 L/min. A follow-up chest CT angiography showed a thrombotic pulmonary embolism. Treatments included curative anticoagulation, antibiotherapy, corticosteroids, and oxygen, leading to improvement after 10 days of treatment. Conclusions This case report highlights that NTPE can occur after all interventional procedures using glue including pelvic procedures and can be complicated by thrombotic pulmonary embolism.